Additional data on the herpetological collection of Louis Amédée Lantz (1886–1953), with emphasis on specimens in the Natural History Museum, London - Ineich, Ivan; Doronin, Igor V.; Cheylan, Marc; Campbell, Patrick D. (Zootaxa, 2019)
Several recent papers have reviewed the life and work of French herpetologist Louis Amédée Lantz. They have detailed the composition of his collections deposited in several museums. However, since then, several other important specimens from his collections deposited at the Natural History Museum (NHM, UK) have come to light and we here present all of them in detail. We discovered paralectotypes of Lacerta saxicola obscura Lantz & Cyrén (BMNH 1918.11.21.5–7), syntypes of Lacerta boemica Sukhov (BMNH 1960.1.4.26–30, BMNH 1965.337–342) and Lacerta viridis media Lantz & Cyrén (BMNH 1960.1.4.25, 1966.512). We also identified numerous specimens from the French Mediterranean islands in Lantz’s collection deposited at the NHM, some of which represent the first reported specimens of their species from certain islands. We here provide data on all these specimens. We also place the Mediterranean island specimens from the Lantz collection in their historical context and emphasize the historical and taxonomic value of these collections.